Lorsque l'écrit décrit le cri de la terre : la Vallée des Cendres comme espace géopoétique dans The Great Gatsby de F. Scott Fitzgerald - Pascal Bardet (Caliban: French Journal of English Studies)
The Valley of Ashes, the archetypal anthropocenic Fitzgeraldian place in The Great Gatsby, is a pallid, fluctuating and elusive environment that irreparably alienates and isolates the individual. It acts as a black hole in which ashes and dust erase all traces of life. The distortion of spatial forms and the anarchic multiplication of movements within the Valley redefine the new American suburban space in F. Scott Fitzgerald's novel. This squalid world on the outskirts of New York testifies to the mechanistic destruction of the land. However, the writer’s apprehension of this augean non-place gives it an aesthetic dimension. The artistic gesture transforms the anthropocenic landscape into a readable object. In this coupling of the real and the imaginary, what Edward Soja calls 'third-space,' geopoetic perspectives appear and transform what seemed to be a 'non-landscape' into an allegorical, transfigured territory.